Aerodynamic Characteristics and Flow Patterns of Square Cylinders with Rounded Facet (MIST International Journal of Science and Technology, 2025)
This study experimentally investigates the effect of facet width on the static pressure distribution around a single square cylinder with rounded facets. Experiments are conducted in an open-circuit wind tunnel at a Reynolds number of 5.4 × 10⁴, based on the side dimension of the cylinder subjected to a uniform flow velocity of 13.6 m/s. Five different  dimensionless  facet  widths are  systematically  introduced  to  assess  their influence  on  pressure  distribution  at  varying angles of  attack.  Static  pressure measurements are collected around the perimeter of the cylinder, and the resulting data are  processed  through  numerical  integration  to  determine  the  corresponding  drag coefficients. The results demonstrate that incorporating facets significantly modifies the aerodynamic characteristics of the cylinder by reducing the drag coefficient compared to that of a sharp-edged configuration. The drag reduction is primarily attributed to delayed flow separation and a decrease in the size of the wake region. However, beyond a critical facet width, further increases produce only marginal improvements, indicating the presence of an optimal range for facet dimensions. This research demonstrates that facet modification is an effective and practical approach for controlling aerodynamic drag in bluff bodies. The findings offer valuable insights for optimizing structural designs subjected to wind loads, highlighting potential applications in civil engineering fields  such  as  building  design,  bridge  construction,  and  tower  development.  By deepening the understanding of how minor geometric alterations can impact flow behaviour, this work contributes to the development of safer, more efficient, and aerodynamically stable structures exposed to atmospheric winds.  MIJST, Vol. 13, June 2025 : 01-08DOI: https://doi.org/10.47981/j.mijst.13(01)2025.547(01-08)